2017
DOI: 10.1126/sciadv.1701469
|View full text |Cite
|
Sign up to set email alerts
|

Lead halide perovskites: Crystal-liquid duality, phonon glass electron crystals, and large polaron formation

Abstract: Efficient dynamic screening is key to the success of lead halide perovskites in solar cells and light emitting devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
443
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(460 citation statements)
references
References 138 publications
(188 reference statements)
17
443
0
Order By: Relevance
“…Furthermore, MAPbI 3 exhibits flexible conductivity from good p-type to intrinsic and to good n-type depending on the chemical potentials (i.e., growth conditions), as shown in Figure 4c. [52,53] Adv. [43] The superior defect tolerance properties of Pb halide perovskites were confirmed by other groups.…”
Section: Excellent Defect Tolerancementioning
confidence: 99%
“…Furthermore, MAPbI 3 exhibits flexible conductivity from good p-type to intrinsic and to good n-type depending on the chemical potentials (i.e., growth conditions), as shown in Figure 4c. [52,53] Adv. [43] The superior defect tolerance properties of Pb halide perovskites were confirmed by other groups.…”
Section: Excellent Defect Tolerancementioning
confidence: 99%
“…[69] Thus, the actual initial HC temperature should be ≈580 K. The scattering of charge carriers with LO-phonons, charge defects, and even with one another can be reduced by the dynamic screening in polar semiconductors. [10,70] They suggested that the large polaron formation rate competes favorably with the initial LO-phonon cooling time to greatly slow down the HC cooling in MAPbBr 3 . [69,[72][73][74] Zhu et al proposed that the dynamical screening from the reorientational motions of the dipolar molecular cations and the large polaron formation give rise to the long-lived HCs in organic-inorganic hybrid perovskites.…”
Section: Large Polaron Formation At Low Carrier Densitymentioning
confidence: 99%
“…Notably, the large energy blueshift and highenergy tail are also present in steady-state PL spectra of FASnI 3 film under high pump-fluence continuous-wave (CW) excitation ( Figure 6d). [70] Copyright 2016, American Association for the Advancement of Science. Such strong emission from HCs under CW operation is an important development toward realizing HCSCs.…”
Section: Band-filling At High Carrier Densitymentioning
confidence: 99%
“…We can estimate the crystal size from Debye-Scherrer equation, given by D size = Kλ/B size cosθ, where D size is Scherrer crystallite size, K is a unit cell geometrydependent constant, λ is the X-ray wavelength (λ = 1.5418 Å), B size is the peak width broadening due to the size effect, and θ is the Bragg angle. [44] In terms of lattices, Mn doping will enable the lattice contraction to slightly increase the bandgap, thus generating a more blue-shifted PL peak. Importantly, different from other films, QNC film with co-addition of FPEAI and Mn 2+ shows (100) plane at 14.26° instead of 14.23° ( Figure S16, Supporting Information), implying the crystal lattice is contracted due to Mn 2+ doping.…”
Section: Resultsmentioning
confidence: 99%